Investigation on the lifespan of gaharu tea: article / Muhammad Syafiq Ridhuan and Habsah Alwi - Ridhuan, Muhammad Syafiq; Alwi, Habsah (2019)
Gaharu tea is a tea that made up from leaves of Aquilaria species. This species has a lot of benefits towards human health such as anti-allergic, anti-diabetic, anti-cancer and anti-inflammatory [1]. In this study, Aquilaria malaccensis has been chosen as the sample due to high distribution of this species in Malaysia. Aquilaria malaccensis is one of the natural species that grow in peninsular Malaysia. This study will investigate the effect of different moisture content and the effect of different storage conditions on the lifespan of gaharu tea. The leaves will be processed using green tea processing method. Based on previous research [5], the drying time is fixed while the temperature and pressure are varied. Therefore, in this research it will undergo drying process at fix temperature (50°C) and pressure (0.6 bar) with different residence time which is 30 mins, 60 mins, 90 mins, 120 mins and 150 mins by using Vacuum Far-Infrared Radiation (VFIR) dryer. After obtained the optimum drying time, the next sample will undergo drying process at fix temperature (50°C), pressure (0.6 bar) and residence time (120 mins) but different storage conditions which is in the kitchen and air conditioning space to determine the optimum lifespan. Lifespan sample will be observed for 4 weeks and the sample will be analyzed every week. All of the samples will be going through moisture content analysis, colony count and chemical analysis. The final result concluded that air conditioning space as the suitable storage condition in order to preserve the nutrient contents.